Eco-Enzyme Sebagai Fondasi P5 Untuk Membangun Entrepreneurship Siswa di SMAN Bolan - Lolita Parera (PT. Penerbit Riset Sadwa, 2025)
Eco-enzyme is a fermentation product of organic waste that offers great potential as a solution for waste management and the strengthening of environment-based entrepreneurship in schools. This community service program aims to increase awareness, skills, and entrepreneurial spirit among students of SMAN Bolan through eco-enzyme production integrated with the P5 Project of the Merdeka Curriculum. Methods include socialization, hands-on eco-enzyme production training, production assistance, entrepreneurial strengthening, and evaluation. The results showed significant improvement in students' understanding and skills in managing organic waste; 90% of students were able to produce eco-enzyme independently and develop simple business plans. The program successfully strengthened collaboration among teachers, students, and the PKM team and established an applicable project-based learning model for replication in other schools. This innovation is crucial in supporting eco-friendly schools and enhancing students' entrepreneurial competencies.